Which capabilities matter for successful business process change?. Issue 1 (28th January 2014) - Christin Jurisch, Marlen; Palka, Wolfgang; Wolf, Petra; Krcmar, Helmut
Abstract : Purpose: – Business process change (BPC) initiatives are complex endeavors, which require many different sets of capabilities from the organization (e.g. IT, change management, project management capabilities). This study aims to examine which capabilities matter for successful BPC. Design/methodology/approach: – The paper posits that a structured analysis of case studies will help in identifying the capabilities relevant for BPC. Against this background, the paper adopted a case survey methodology, which combines the richness of case studies with the benefit of analyzing large quantities of data. The paper identified and analyzed 130 case studies reporting the past BPC project experiences. Findings: – The results show that project management, change management and IT capabilities have a positive impact on BPC project performance. IT capabilities also have a positive impact on the final process performance. Thus, IT capabilities matter for both BPC project and process performance. Research limitations/implications: – The study had a few limitations, such as the use of secondary data. More so, assigning numbers to qualitative data unduly simplifies the complex phenomena under investigation and may leave out some of the richness of case research. Practical implications: – The findings provide considerable support for determining which capabilities practitioners need to leverage and develop when improving their business processes. Originality/value: – The study makes a number of contributions. It fills a gap in the literature concerning which capabilities matter for successful BPC. The paper offers a theoretical explanation of the effects of capabilities on the BPC project and process performance. Another contribution is methodological, in that the paper adopted the case survey method, which is still new to information systems research.